Spatiotemporal Variations of Human Pressure on Key Biodiversity Areas in the Qinghai–Tibet Plateau: A Comparative Analysis - Zeng, Yuxi; Wang, Ling-en; Zhong, Linsheng (Frontiers in Ecology and Evolution, 2022)
Key biodiversity areas (KBAs) are an emerging area-based conservation measure that have recently been introduced in China, but human pressure faced by KBAs is still unclear. Taking the Qinghai-Tibet Plateau as an example, this study analyzed the spatiotemporal variation of human pressure on KBAs from 1990–2017 and compared it with the human pressure on national natural reserves (NNRs). On this basis, changes in the trend of human pressure before and after 2010 were further analyzed to examine the influence of conservation policies on human pressure. Results showed that human pressure on KBAs and NNRs gradually increased from 1990–2017. Further, the growth rates and mean values of human pressure in KBAs were higher than those in NNRs. After implementation of conservation policies in 2010, the growth rates of human pressure on both KBAs and NNRs have significantly slowed, and the areas with negative growth in both KBAs and NNRs have gradually expanded. In addition to understanding the changing spatiotemporal trends of human pressure on KBAs, this study can inform policies to improve conservation effectiveness.